Interactive toy for cognitive stimulation of neurodivergent children: product development following the Product Development Process (PDP) - Santos, Beatriz de Jesus dos; Freitas, Alina de Oliveira; Santos, Andre de Mendonça; Alves, Lucas Vitorino; Barreto, Óliver Silva Costa (Brazilian Journal of Production Engineering, 2025)
The neurodiversity paradigm has driven the creation of solutions that promote inclusive cognitive development. Although the toy sector is expanding, there is still a shortage of products that combine safety, multisensory stimulation, and methodological rigor. This article presents the adapted application of the Product Development Process (PDP) in the design and prototyping of a sensory maze aimed at neurodivergent children. The methodology used quality tools such as QFD, the morphological matrix, and FMEA, which were essential for translating complex user needs into technical requirements that ensured engagement, safety, and pedagogical effectiveness. The project prioritized materials such as ABS and acetate, rounded edges, and interactive LED pathways. Additive manufacturing enabled the development of a 3D polymer prototype and the identification of failures prior to production. As a limitation, the study highlights the absence of usability testing, indicating directions for future research.